2020
DOI: 10.3892/or.2020.7479
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin variants are expressed in human glioblastoma cells‑hypoxia effect?

Abstract: Glioblastoma multiforme (GBM) is the most aggressive human brain cancer. Little is known regarding how these cells adapt to the harsh tumor microenvironment, and consequently survive and resist various treatments. Myoglobin (MB), the oxygen-binding hemoprotein, has been shown to be ectopically expressed in different human cancers and cell lines, and its expression is hypothesized to be an adaptation mechanism to hypoxia. The aim of the present study was to determine whether cancer-related and hypoxia-responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…The relative fold change in mRNA of target genes for each cell line was calculated as previously described. [ 33,34 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative fold change in mRNA of target genes for each cell line was calculated as previously described. [ 33,34 ]…”
Section: Methodsmentioning
confidence: 99%
“…The fold change in mRNA of target genes for each cell line was calculated as previously described. [33,34] 2.9 | Determination of H 2 O 2 produced by PAAWM Amplex UltraRed reagent (Catalog no. A36006, Molecular Probes, Thermo Fisher Scientific, Inc.) was used to determine H 2 O 2 produced by PAAWM.…”
Section: Rt-quantitative Pcr (Qpcr)mentioning
confidence: 99%
“…We have previously reported that neuroglobin (Ngb) and cytoglobin (Cygb) are expressed in human GBM cells, various solid tumors, and various brain cancers and their corresponding normal adjacent tissues with hemoglobins (HB) being also expressed in human GBM cells (4,(22)(23)(24)(25). Recently, we have reported that MB variants 2, 9, 10, 11, 13 are differentially expressed in GBM cells (26). In continuation of our previous work, we sought to investigate MB expression and its correlation with hypoxia markers: CAIX and lactate dehydrogenase A (LDHA), in human tissue microarrays (TMA) of multiple organ tumors, different brain tumors, and GBM tissue samples and their relative cancer-adjacent normal tissues (CANT).…”
Section: Introductionmentioning
confidence: 99%